EMOTIONAL INTELLIGENCE AS THE MAIN RESOURCE OF WILLINGNESS OF TEACHERS-PSYCHOLOGISTS STUDENTS TO THEIR PROFESSIONAL ACTIVITY - A.S. Smykov; Z.K. Kulsharipova; D.S. Akhmetova; K.D. Baklanova (Foundations and Trends in Research, 2024)
At the present stage of society development, the requirements for the education system, the training quality and the formed level of professionally significant characteristics, largely laid at the university, are increasing. Professional success of an individual is undoubtedly associated with knowledge, skills, erudition and ability to think in general, that is, with the level of general intelligence. However, in most cases, a high level of general intelligence is not enough. The idea of emotional intelligence was a consequence of the development of ideas about social intelligence, the main reason for distinguishing it as an independent ability or trait was the frequent discrepancy between the level of general intelligence and the success of the individual in interacting with the educational environment at the university. Emotional intelligence is one of the most important factors determining the productivity of future specialists and mediates the humanistic orientation of the individual approach in personal development and training, self-acceptance, and personal maturity. The author's position is the need to search for the foundations of the development of emotional intelligence among students in order to solve professional problems.